Penholding Power and P3 Dominance: A Critical Examination of Misuse in the UN Security Council - Elamin, Mustafa Osman I. (Journal of Cultural Analysis and Social Change, 2025)
This paper critically examines the misuse of the United Nations Security Council’s penholding system by the three permanent Western members, the United States, the United Kingdom, and France (P3). Through two in-depth case studies, Sudan/Darfur (1996–present) and Syria humanitarian access (2011–2024), it argues that penholding has evolved from an informal procedural convenience into a mechanism of sustained political control. The study draws on primary UN sources, including meeting records and resolutions, as well as secondary academic literature and NGO reports, to assess how P3 penholding practices marginalize regional actors, instrumentalize legal and humanitarian instruments, and entrench file ownership without clear exit strategies. In Sudan, the UK’s takeover of penholding from African members in 2004 marked a shift from time-bound, compliance-linked measures to prolonged agenda control, selective justice (as in the ICC carve-out of Resolution 1593), and strategic framing that excluded inconvenient allegations. In Syria, P3 penholding over humanitarian access embedded political blame narratives into aid resolutions and resisted meaningful co-penholding with elected or regional members. The findings highlight the structural drivers of misuse, informality, capacity asymmetry, and veto politics, and propose reforms, including codified rotation, genuine co-penholding, and regional leadership prioritization. The paper concludes that without such reforms, penholding will remain a barrier to inclusivity, impartiality, and legitimacy in Council decision-making.